Approach to the Investigation and Management of Patients With Candida auris, an Emerging Multidrug-Resistant Yeast. (17th August 2017) - Tsay, Sharon; Kallen, Alexander; Jackson, Brendan R; Chiller, Tom M; Vallabhaneni, Snigdha
Abstract : Candida auris is an emerging, multidrug-resistant yeast that can spread in healthcare settings. This review summarizes the current recommended approach to manage cases and control transmission of C. auris in healthcare facilities. Abstract: Candida auris is an emerging, multidrug-resistant yeast that can spread in healthcare settings. It can cause invasive infections with high mortality and is difficult to identify using traditional yeast identification methods. Candida auris has been reported in more than a dozen countries, and as of August 2017, 112 clinical cases have been reported in the United States . Candida auris can colonize skin and persist in the healthcare environment, allowing for transmission between patients. Prompt investigation and aggressive interventions, including notification to public health agencies, implementation of contact precautions, thorough environmental cleaning and disinfection, infection control assessments, contact tracing and screening of contacts to assess for colonization, and retrospective review of microbiology records and prospective surveillance for cases at laboratories are all needed to limit the spread of C. auris . This review summarizes the current recommended approach to manage cases and control transmission of C. auris in healthcare facilities.